1998
DOI: 10.1902/jop.1998.69.3.383
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Gingival Recession With Titanium Reinforced Barrier Membranes Versus Connective Tissue Grafts

Abstract: It was the aim of this study to compare barrier membrane therapy with connective tissue grafts in the treatment of recession defects. Fifteen patients with 2 paired vestibular recession defects participated in the study. After thorough scaling and root surface conditioning with tetracycline-HCl, defects were randomly assigned to 1 of 2 treatment modalities. In one of the defects, a trapezoidal mucoperiosteal flap was prepared, and a titanium reinforced expanded polytetrafluoroethylene membrane was adapted to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
3
12

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(118 citation statements)
references
References 29 publications
8
95
3
12
Order By: Relevance
“…38 Postoperative membrane exposure has been shown negatively related to the amount of root coverage achieved. 39 In our study, none of GTRC-treated sites had membrane exposure due to the efforts made to relieve the inherent tissue tension, obtaining primary coverage without any tension.…”
Section: Discussionmentioning
confidence: 63%
“…38 Postoperative membrane exposure has been shown negatively related to the amount of root coverage achieved. 39 In our study, none of GTRC-treated sites had membrane exposure due to the efforts made to relieve the inherent tissue tension, obtaining primary coverage without any tension.…”
Section: Discussionmentioning
confidence: 63%
“…56,59 Furthermore, membrane exposure may impair the amount of root coverage expected. One paper evaluating the results achieved with non-resorbable membranes 50 reported mean root coverage of 75% in defects with membrane exposure, as opposed to a mean root coverage of 97% in defects where membrane exposure did not occur. It appears that the elimination of the re-entry procedures may prevent the risks of mechanical trauma to the newly formed tissue during the early phases of healing process, while avoiding a second surgical stress for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31][32][33][34] Three RCTs reported the results from samples containing less than 10 patients per group at final examination, 13,35,36 two studies were classified as randomized non-controlled trials, 37,38 two presented a follow-up period <6 months, 39,40 two did not present a patientbased analysis 41,42 and one included recession areas containing teeth with restorations. 43 Of the 23 included studies, 5,12,15,44-63 fifteen had a splitmouth group study design 5,15,[44][45][46][40][41][42][43][44][45][46][47][48][49][50][51][52][53]57,58,[60][61][62]63 and seventeen were conducted at university dental clinics 5,12,44,…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most studies that compared GTR and SCTG concluded that SCTG resulted in statistically better root coverage, width of keratinized gingiva, and complete root coverage. [76][77][78][79] Tenyear follow-up comparing SCTG and GTR for root coverage found that the long-term stability of root coverage (ie, the reduction of recession depth) and esthetic results perceived by patients were significantly better using SCTG compared with GTR surgery using bioabsorbable barriers. 80 …”
Section: Guided Tissue Regenerationmentioning
confidence: 99%